Assessing the Risk of Groundwater Contamination from Farm & Home Waste Management - Herbel, Kevin L.; Powell, Morgan G. (Kansas State University, 1998)
To determine the variety of products used around the farm and how to dispose of them to prevent contaminating groundwater.
EP46_1998-08
Keywords: EP46; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP